The Impacts of COVID-19 Crisis over the Tourism Expectations of the Azores Archipelago Residents - Couto, Gualter (2020)
Throughout history, times of crisis have always been preceded by periods of change. In fact, the current moment of health, economic, and social crisis that we are experiencing seems to be no exception. Tourism seems to be one of the most a ected activities by the COVID-19 pandemic crisis—due not only the cancelled flights but also to the fear of being infected with the virus. In this sense, the present article intends to identify the Azores Archipelago residents’ tourism expectations during the COVID-19 crisis. Using the Azores Islands as a case study and merging it with the authors’ knowledge about this regional reality, it was possible to collect a substantial quantity of data. Thus, this study provides an in-depth perception of the main issues about how this pandemic crisis a ects the tourism expectations of the Azores region residents, and consequently, how this situation will influence regional sustainable development. Through the study, it was possible to verify that the significant part of the Azores Archipelago residents (57.5%) will not be going to travel to spend vacations in 2020. Additionally, 84.2% will have holidays in the region; therefore, they stay in the Azores Archipelago. Besides, this study shows that majority of the respondents (61.6%) would not make a reservation for a 2020 vacation.